Effectiveness of adsorption of alizarin red s and alizarin yellow 2G from aqueous solutions using zeolite L - Insuwan, Wilaiporn; Srihongthong, Saowaluck; Permngam, Navaphum; Tongkasee, Pongsathorn (Agriculture and Natural Resources, 2023)
Importance of the work: Zeolite L in potassium form (KLTL) was used as an alternative adsorbent for the adsorption of alizarin red s (ARS) and alizarin yellow 2G (ARY) from aqueous solutions. Objectives: To use KLTL as an alternative adsorbent for the removal of two anionic dyes from aqueous solutions. Materials & Methods: The adsorption performance was determined by adsorption equilibrium, kinetics, and thermodynamic parameters. Results: The optimum adsorbent dosage and contact time were 0.025 g and 120 min, respectively. The adsorption isotherm and kinetics followed the Langmuir isotherm, the maximum monolayer adsorption capacity was 95.24 mg/g and 41.30 mg/g for ARS and ARY, respectively, while the mechanism of adsorption followed a nonlinear pseudo-firstorder model. All anionic dyes were adsorbed onto KLTL via an electrostatic interaction and H-bond. In addition, thermodynamic parameters such as ΔG°, and ΔH° were investigated and suggested that the adsorption of the anionic dyes onto KLTL was the spontaneous and endothermic reaction. Main finding: This was the first study on the adsorptive removal of the anionic ARS and ARY dyes using KLTL as an adsorbent. The results of the study are important for industrial applications.